Pengaruh Model CLIS Terhadap Hasil Belajar Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Annisa Aulia; Alizar Ulianas (Universitas Negeri Padang, 2020)
An experimental research using the Children Learning In Science (CLIS) model has been conducted to figure out learning outcome. The research sample involved two classes with different learning model. The first class model used the CLIS model as experimental class while the second class model used the conventional model as a control class. Multiple choice questions were the research instrument to measure students achievement in cognitive aspect. The results showed that the average of the experimental class was 85,29 and the control class was 78,43. The study showed that the CLIS model has positive and significant influence on the student learning outcomes.